Realization of trophy shaped flexible wearable antenna based on foam substrate - Dubey, Reema; Kumar Singh, Vinod; Kumar Bhoi, Akash; Ali, Zakir (International Journal of Engineering and Technology, 2018)
The endeavor of this paper is to analyze a light weighted flexible antenna for modern communication system. There are three different patch designs with operating frequency 4GHz. These proposed antennas are compact in size, shows high directivity and large bandwidth. Ex-pandable polystyrene foam is used as a substrate because such antenna are bendable, wearable, cheap, require less attention and having good features like low dielectric constant, low loss tangent and better efficiency. The antenna parameters like reflection coefficient, gain, band-width, radiation pattern are analyzed. The reflection coefficient of anticipated antenna provides a good concurrence between simulated and measured result. Foam based design is simulated by using CST studio.Â